Modelling of degenerative changes in paravertebral muscles for studying of its influence on spine diseases - Radchenko, Volodymyr; Leontyeva, Frieda; Tuliakov, Vladyslav; Skidanov, Mykyta; Skidanov, Artem; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
An important component of the development of degenerative changes in the spine is damage and disruption of the vital activity of the paravertebral muscles. Objective. Based on the analysis of biochemical parameters of laboratory rats serum we evaluated the suitability of the studied models of dystrophic muscle tissue lesions for further study of the development of degenerative-dystrophic disorders in the spinal motor segments. Methods. Simulated: group I (5 female rats) — alimentary obesity by keeping for 3 months. on a high-calorie diet (hyperlipidemic diet); group II (5) — ischemia by ligation for 45 days of large back rectus muscles the with suture material that is not absorbed. Control — 5 intact animals of the same age and sex, which were kept on a standard diet. Serum levels of glycoproteins, haptoglobin, total chondroitin sulfates (CHS), glucose, cholesterol, low-density lipoproteins, triglycerides, total lipids, activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline and acid phosphatases, creatine phosphokinase were defined, thymol test was determined. Parameters were processed by the Fisher–Student method. Results. In the I group of rats, the content of glycoproteins, total cholesterol and lipids, low-density lipoproteins, triglycerides, glucose, CHS, ALT and AST activity, thymol test values were increased and the level of creatine phosphokinase activity was decreased. In animals of group II, an increase in serum activity of creatine phosphokinase, glycoproteins and CHS was recorded. Conclusions. Changes in the serum biochemical parameters of white rats recorded on a hyperlipidemic diet indicate the development of fatty degeneration, including in muscle tissue. Biochemical signs of degenerative processes in muscle tissue have been identified as a result of simulation of paravertebral muscle ischemia. Key words. Muscle, disorders, degeneration, spine, modeling, hyperlipidemia, ligation, biochemistry.